Relevance of obesity-related organ damage and metabolic syndrome classification in cardiovascular and renal risk stratification in patients with essential hypertension - Luigi Petramala; Antonietta Gigante; Francesca Sarlo; Adriana Servello; Francesco Circosta; Luca Marino; Luca Marino; Antonello Ciccarelli; Giuseppe Cavallaro; Giuseppe Cavallaro; Claudio Letizia (Frontiers in Cardiovascular Medicine, 2024)
IntroductionHypertension is a relevant cardiovascular comorbidity. Adipose tissue represents a metabolically active tissue involved in the regulation of blood pressure and metabolic alterations. In recent decades, several classifications for the metabolic syndrome (MS) have been proposed. Recently, a new syndrome called the “Cardiovascular-kidney-metabolic” (CKM) syndrome was identified, to determine patients at high cardiovascular and metabolic risk. The aim of the study was to compare different classifications in a large population of hypertensive patients.Materials and methodsBetween September 2022 and August 2023, we consecutively enrolled 772 hypertensive patients (407 men; 365 women; mean age 52.2 ± 15.1 years), evaluating anthropometric, biochemical, and instrumental parameters (transthoracic echocardiogram, carotid echo-Doppler, 24-h ambulatory blood pressure monitoring, fundus oculi).ResultsUsing different classifications we found MS prevalence: Adult Treatment Panel III (ATP-III) 28.8%, International Diabetes Federation (IDF) 31.5%, CKM 40.7%. CKM Classes 3 and 4 showed higher body mass index and waist circumference compared with other groups. Compared with ATP-III and IDF, CKM Class 4 showed higher 24-h systolic blood pressure, lower percentage of controlled hypertension, increased interventricular septum and posterior wall, reduced ejection fraction, and greater prevalence of hypertensive arterial retinal damage.DiscussionVisceral obesity and MS are frequent conditions with healthy impact, becoming an important trigger for the development of cardiovascular and metabolic complications. The different MS classifications allow the early identification of patients at high risk of cardiometabolic complications. The new CKM syndrome proves useful to identify individuals at high risk for CKM morbidity and mortality.